Epidemiological investigations of tinnitus - Biswas, Roshni (2021)
Subjective tinnitus is defined as the conscious perception of an auditory sensation in the absence of a corresponding external stimulus. Severe tinnitus can significantly affect physical and mental well-being while incurring substantial social and financial costs on the individual and society. Nonetheless, tinnitus research and financial investment are substantially lower than other comparable conditions. Adequate assessment of tinnitus prevalence and investigating tinnitus-related risk factors could help recognise the burden of tinnitus and the need for adequate resource allocation. Understanding the epidemiology of tinnitus is crucial for addressing the population-level questions and identifying and quantifying exposures that predispose an individual to tinnitus.